Government-third sector relations in European rural development: A critical perspective - Constantine Iliopoulos; Vladislav Valentinov; Vasyl Kvartiuk; Bartosz Bartkowski (Nonprofit Policy Forum, 2013)
Rural development has significantly benefited from intensifying relations between the government and third sector organizations (TSOs) during the last several decades. TSOs can induce innovation in rural development in a variety of ways including advocacy, awareness raising, contracting, and direct delivery of public goods. However, there is a growing concern that these partnerships may be prone to inefficiencies due to adverse fundraising incentives. Utilizing Young's (2000) typology in a literature review, this paper illuminates potential causes for mission and goal displacement due to adverse incentives generated by public funding programs. The paper suggests that complementary and supplementary TSOs are generally more likely to suffer from adverse incentives in comparison to adversarial ones. Institutional merging between the TSOs and the state may significantly limit the scope for innovation in rural development.
Keywords: 330; third sector organizations; rural development; Europe